2002
DOI: 10.1046/j.1365-2249.2002.01742.x
|View full text |Cite
|
Sign up to set email alerts
|

Thein vivoeffects of tumour necrosis factor blockade on the early cell mediated immune events and syndrome expression in rat adjuvant arthritis

Abstract: SUMMARY Anti‐TNF therapy is effective in rheumatoid arthritis (RA); however, its mechanisms of action are incompletely understood. T cell‐driven mechanisms are thought to play an important role in RA and the effects of TNF blockade on these mechanisms are unclear. Adjuvant arthritis (AA) is a T cell dependent model of inflammatory arthritis. The aims of this study were to investigate the effects of TNF blockade on in vivo T cell cytokine expression and to clarify the role of TNF in the inguinal lymph nodes (IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…Similarly, the treatment of rats with sTNF-RI beginning on day 4 after disease onset induced suppression of AA [30]. By contrast, in another study, sTNF-RI treatment of DA rats on days 0, 2, and 4 post-Mtb injection had no significant effect on early phase of AA [31]. However, later in the course of AA, lower dose of sTNF-RI exacerbated AA, while higher dose failed to alter the disease severity, supporting a concentration-dependent biologic effect of this pro-inflammatory cytokine [31].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the treatment of rats with sTNF-RI beginning on day 4 after disease onset induced suppression of AA [30]. By contrast, in another study, sTNF-RI treatment of DA rats on days 0, 2, and 4 post-Mtb injection had no significant effect on early phase of AA [31]. However, later in the course of AA, lower dose of sTNF-RI exacerbated AA, while higher dose failed to alter the disease severity, supporting a concentration-dependent biologic effect of this pro-inflammatory cytokine [31].…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α injection of TNFR1-deficient mice in early initiation phase of CIA aggravated the disease, whereas TNF-α administration in late initiation phase suppressed arthritis, again pointing to the opposite stage-dependent effects of this cytokine [66]. A study employing in vivo neutralization of TNF-α in the AA model also revealed differential effects on arthritis of the dosage as well as the timing of administration of sTNFR [67]. Taken together, these studies highlight the significance of the effects of temporal variations in TNF-α production during the course of arthritis and the resulting effects of the in vivo blockade of the cytokine.…”
Section: Experimental Downmodulation Of Arthritis and Other Autoimmunmentioning
confidence: 99%
“…The treatment with A 2A AR agonists decreased the expression of inflammatory cytokines and the degree of oxidative and nitrosative damage [25]. Adjuvant-induced arthritis is a commonly used model of inflammatory arthritis, with an incidence of around 90%, making it an ideal model in which to investigate arthritic changes and to evaluate compounds that might be of potential use as drugs for RA treatment [26], [27]. Recently, A 2A AR agonists have been approved for clinical trials based on their anti-inflammatory and wound-healing properties [15], [28], [29].…”
Section: Introductionmentioning
confidence: 99%